Sistem Pendukung Keputusan Penerima Bantuan Pandemi Menggunakan Metode AHP (Analytical Hierarchy Process) - Sister P Lumbantoruan (Institute of Computer Science (IOCS), 2021)
The Covid-19 pandemic has had a negative impact on the Indonesian economy, thus prompting the government to pay great attention to the people at the grassroots level by holding aid programs. There are problems that occur in determining the recipients of assistance, namely there are criticisms and rejections regarding the inappropriateness of the target of assistance and there are obstacles faced by village officials in collecting data and determining which beneficiaries are prioritized or prioritized with those that are not prioritized, so that it is not in accordance with the Government's expectations that families Vulnerable categories are prioritized beneficiaries that should not be missed. Researchers think about implementing a Decision Support System using the AHP (Analytical Hierarchy Process) method in this problem with the aim of knowing how to implement a Decision Support System in the problem of determining beneficiaries during a pandemic and to find out how to apply the AHP method in determining prioritized or prioritized recipients or those who are not. not prioritized by utilizing criteria and alternative data. This study uses a quantitative method, where the application of the AHP method, the criteria and alternative data obtained will be converted into quantitative data through pairwise comparisons based on the level of importance between one criterion and another or a comparison between one alternative and another, so that the results obtained are quantitative value in the form of numbers. The results obtained are that the application of the AHP method can determine the priority weights of criteria and alternatives so that it can be determined which recipients are prioritized and who are not prioritized to receive assistance, namely there are 2 out of 5 alternatives with the highest priority weights that are prioritized to receive assistance.